Implementasi Metode Advanced Encryption Standard (Aes) dalam Mengamankan Data File Soal Ujian SMK Media Informatika Berbasis Web - Mega Nur Utami; Bani (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2026)
The rapid development of information and communication technology has brought significant impacts, both positive and negative. One of the main challenges is data security. Organizations, educational institutions, and companies face high risks of data interception and information leaks that threaten privacy and system integrity. Although storing student exam files in softcopy form offers efficiency, weaknesses in security still pose risks of cyber-attacks such as hacking, malware, and data theft. In this context, SMK Media Informatika Jakarta places a high emphasis on the security of exam data, which is sensitive and must not be accessed before the exam schedule. Storage without adequate protection can lead to significant damage. Therefore, advanced digital security strategies are necessary. One recommended solution is the use of cryptography, specifically the Advanced Encryption Standard (AES) method. Cryptography secures data by encrypting files, making them accessible only to authorized parties. This study proposes the implementation of the AES method to secure web-based exam files at SMK Media Informatika Jakarta, providing an additional layer of protection and ensuring that sensitive information remains safe from unauthorized access, while also allowing secure and controlled access for authorized users.